If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 7 = 14x Reorder the terms: 7 + 15x = 14x Solving 7 + 15x = 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 7 + 15x + -14x = 14x + -14x Combine like terms: 15x + -14x = 1x 7 + 1x = 14x + -14x Combine like terms: 14x + -14x = 0 7 + 1x = 0 Add '-7' to each side of the equation. 7 + -7 + 1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 0 + -7 1x = 0 + -7 Combine like terms: 0 + -7 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 0.05a+0.09(a+5000)=7.6 | | d/dx(sin(pi/3)) | | 162=12x+0.5x^2 | | (6/(x-9))-(10/(x=3))=3 | | Grafiky=-5x-4 | | x:2(x-4)1/2(5-3x) | | TC=4+8Q+0.6Q^2 | | 2+3(x+1)=7 | | (6/(x-9))-(9/(x-7))=-15 | | r(x)=-x-7 | | 3(6-x)=27/6-6 | | (x-5)(4x-3)=(1-3x)(x+1) | | 8/1.3*100/x | | (x-6)(3x-2)=(2x-3)(x-10) | | (x+3)(x-5)=(x+3)(x+3) | | (x+3)(x-5)=(x+3)x(x+3) | | 0.4a+0.7(13-a)=7.6 | | 9=-9b+2b | | 2x-35=2x+9 | | 9n-36=-18 | | 4(x-3)=12(x-5) | | p-9=-6p-3 | | 2x+20+4x-10=180 | | 3(x+4)-4=3(x-4) | | 0.25y=12 | | 3(x-4)-4=3(x-4) | | lnx=22.87 | | 2.5(fk+2)=12k | | 4x+3x=182 | | y^6-3y^4-y^3+3y^2-1=0 | | -6(6x-1)=-36x-6 | | 144x^2-1/4=0 |